DAMPAK PERUBAHAN PERILAKU KONSUMEN SAAT PANDEMI COVID-19 PADA PENINGKATAN PENJUALAN BISNIS E-COMMERCE DI KABUPATEN SUMENEP - Istiyanatul Mahbubah; Sofie Yunida Putri (Behavioral Accounting Journal, 2021)
COVID-19 has resulted in various business sectors, especially MSMEs facing far greater challenges and uncertainties than before, so it is necessary to build greater adaptability through the digitalization process, a challenge for all business sectors to operate efficiently and safely. In addition, one way that can help them maintain efficiency and safe operations during the pandemic is to adopt digitalization or start switching from conventional trading methods to online trading, which is often known as electronic commerce (e-commerce). This spending medium is not new. However, due to the limitations and restrictions that existed during the pandemic, consumers tend to experience changes in shopping behavior, so of course this will affect the increase in e-commerce business sales. The study aims to identify how the impact of changes in consumer behavior during the COVID-19 pandemic on increasing sales of e-commerce businesses in Sumenep Regency. The method used in this research is quantitative using SPSS. The conclusion of this study states that there is a change in consumer behavior due to the COVID-19 pandemic which has an effect on increasing sales of E-Commerce business in Sumenep Regency. Which means that the pandemic has resulted in an increase in income for e-commerce business players, when compared to before the COVID-19 pandemic.